2019
DOI: 10.1111/epi.16388
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cannabinoid 2 receptor activity increases susceptibility to induced seizures in mice

Abstract: Objective: The endocannabinoid system (ECS) is comprised of cannabinoid receptors 1 and 2 (CB1R and CB2R), endogenous ligands, and regulatory enzymes, and serves to regulate several important physiological functions throughout the brain and body. Recent evidence suggests that the ECS may be a promising target for the treatment of epilepsy, including epilepsy subtypes that arise from mutations in the voltage-gated sodium channel SCN1A. The objective of this study was to explore the effects of modulating CB2R ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 68 publications
(170 reference statements)
0
31
0
Order By: Relevance
“…Likewise, in the pilocarpine rat model, CB2R expression was upregulated in the hippocampus following SE [ 204 ]. Taken together, both these studies suggest a putative neuroprotective action of eCBs via CB2R in epilepsy [ 203 , 204 ].…”
Section: Cannabinoids and The Endocannabinoid Systemmentioning
confidence: 97%
See 2 more Smart Citations
“…Likewise, in the pilocarpine rat model, CB2R expression was upregulated in the hippocampus following SE [ 204 ]. Taken together, both these studies suggest a putative neuroprotective action of eCBs via CB2R in epilepsy [ 203 , 204 ].…”
Section: Cannabinoids and The Endocannabinoid Systemmentioning
confidence: 97%
“…More recently, CB2R has also been shown to be systemically activated to modulate immune-mediated symptoms associated with seizure-induced-neuroinflammation [ 199 , 200 ] (reviewed in References [ 201 , 202 ]). Interestingly, CB2R knockout mice exhibited an increased susceptibility to induced seizures [ 203 ]. Likewise, in the pilocarpine rat model, CB2R expression was upregulated in the hippocampus following SE [ 204 ].…”
Section: Cannabinoids and The Endocannabinoid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from ambiguity over the CB1R’s role in the prevention of epileptic seizures, and the potential to induce psychological adverse effects, there is also some concern over the effectiveness of targeting CB1R solely as a therapeutic strategy [ 360 , 361 ]. By employing animal and cell culture models of epilepsy, several studies have demonstrated that CB2R is involved in conferring a protective phenotype to a variety of seizure types [ 362 , 363 , 364 ]. CB2R, which is primarily expressed on activated microglial cells, induced astroglial cell proliferation and survival in an astrocyte model of epilepsy [ 363 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%
“…In this study, we adopted an acute pentylenetetrazole (PTZ) paradigm to induce seizures in control and Fb Ctgf KO mice. PTZ is a bicyclic tetrazol derivative that suppresses GABAergic neurotransmission and has long been used for inducing convulsions and seizures in various animal models [ 26 , 27 , 28 , 29 , 30 ]. We scored PTZ-induced seizure behaviors and measured c-fos expression as well as glial responses in the mouse brain.…”
Section: Introductionmentioning
confidence: 99%